2014
DOI: 10.1002/ejlt.201400206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and refining of sunflower biodiesel in a cascade of continuous centrifugal contactor separators

Abstract: The synthesis of fatty acid methyl esters (FAME) from sunflower oil and methanol was studied in a continuous centrifugal contactor separator (CCCS) using sodium methoxide as the catalyst. The effect of relevant process variables like oil and methanol flow rate, rotational speed and catalyst concentration was investigated and modelled using non-linear regression. Good agreement between experiments and model were obtained. At optimised conditions (oil flow rate of 31 mL/min, rotational speed of 34 Hz, catalyst c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The sunflower oil was purchased from Deli XL (Reddy), the Netherlands. The fatty acid composition, acid value, water content and phosphorus content of the oil has been determined and is reported in . The oil was analysed by GC and shown to consist mainly of linoleic acid (57.4%), oleic acid (30.2%), palmitic acid (8.4%) and stearic acid (4.0%).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sunflower oil was purchased from Deli XL (Reddy), the Netherlands. The fatty acid composition, acid value, water content and phosphorus content of the oil has been determined and is reported in . The oil was analysed by GC and shown to consist mainly of linoleic acid (57.4%), oleic acid (30.2%), palmitic acid (8.4%) and stearic acid (4.0%).…”
Section: Methodsmentioning
confidence: 99%
“…We have also modified the CCCS type CINV V02 to achieve a higher biodiesel volumetric production rate at a given FAME yield (2470 kg FAME /m3 reactor · h for 94 mol% yield). Proof of principle for the synthesis and subsequent refining of FAME in a cascade of two CCCS devices has also been demonstrated . Phase separation between the biodiesel and water in the crude biodiesel washing unit (a second CCCS) was excellent at low flow rates.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of these advantages, CCS is very suitable for continuous separation of enantiomers by ELLE. CCS has been successfully used for the synthesis and refining of biodiesel, for separation of ionic liquid dispersions, for oil‐water separation, and for several other extraction processes . Although the separation of enantiomers by multistage ELLE in CCS has attracted increasing attention in recent years, studies on experimental and modeling of the multistage ELLE have been rarely reported …”
mentioning
confidence: 99%